Evaluation of Reactive Power Support Capability of Wind Turbines - Chung, P. D. (Engineering, Technology & Applied Science Research, 2020)
Reactive power plays an important role in the operation of power systems, especially in the case of wind energy integration. This paper aims to evaluate the reactive power support capability of wind turbines in both normal and voltage sag conditions. The three 2MW wind turbines studied are a fixed speed wind turbine and two variable speed wind turbines with full-scale and power-scale power converters. Comparison results indicate that at normal operation, the fixed speed wind turbine with a static synchronous compensator is able to consume the highest reactive power, while the variable speed wind turbine with full-scale power converter can supply the highest reactive power. In case of low voltage, the fixed speed wind turbine with the static synchronous compensator can support the highest reactive power if the static synchronous compensator’s capacity is similar to the wind turbine’s capacity, while if its capacity is equal to 25% of the generator’s capacity, the variable speed wind turbine with full-scale power converter has the best performance.